Evaluation of the effectiveness of sleep hygiene education and FITBIT devices on quality of sleep and psychological worry: a pilot quasi-experimental study among first-year college students - Bani Issa, Wegdan; Hijazi, Heba; Radwan, Hadia; Saqan, Roba; Al-Sharman, Alham; Samsudin, A. B. Rani; Fakhry, Randa; Al-Yateem, Nabeel; Rossiter, Rachel C.; Ibrahim, Ali; Moustafa, Ibrahim; Naja, Farah; et al. (Frontiers in Public Health, 2023)
Background: College students report disturbed sleep patterns that can negatively impact their wellbeing and academic performance. Objectives: This study examined the effect of a 4-week sleep hygiene program that included sleep education and actigraph sleep trackers (FITBITs) on improving sleep quality and reducing psychological worry without control group. Design, settings and participants: A pilot quasi-experimental design, participants were randomly selected medical and health sciences from a university students in the United-Arab-Emirates. Methods: Students were asked to wear FITBITs and log their daily sleep data and completed the Pittsburgh Sleep Quality Index (PSQI) and Penn State Worry Questionnaire (PSWQ). Extensive sleep hygiene education was delivered via lectures, a WhatsApp group, and the Blackboard platform. In total, 50 students completed pre-and post-assessments and returned FITBIT data. Results: There was a significant difference in the prevalence of good sleep postintervention compared with pre-intervention (46% vs. 28%; P=0.0126). The mean PSQI score was significantly lower post-intervention compared with pre-intervention (6.17±3.16 vs. 7.12.87; P=0.04, Cohen's d 0.33). After the intervention, subjective sleep quality, sleep latency, and daytime dysfunction were significantly improved compared with pre-intervention (P<0.05). In addition, FITBIT data showed total sleep time and the number of restless episodes per night were significantly improved postintervention compared with pre-intervention (P=0.013). The mean PSWQ score significantly decreased from pre-intervention to P=0.049, Cohen' d=0.25). The correlation between PSQI and PSWQ scores was significant post-intervention (β=0.40, P=0.02).Our results may inform university educational policy and curricular reform to incorporate sleep hygiene awareness programs to empower students and improve their sleep habits.